Putting the Puzzle Back Together—A Narrative Case Study of an Athlete Who Survived Child Sexual Abuse in Sport - Gillard, Allyson; St-Pierre, Elisabeth; Radziszewski, Stephanie; Parent, Sylvie (Frontiers in Psychology, 2022)
Denunciations of child sexual abuse (CSA) in the sport context have been increasing in the last decades. Studies estimate that between 14% to 29% of athletes have been victim of at least one form of sexual violence in sport before the age of 18. However, studies suggest that many do not disclose their experience of CSA during childhood. This finding is alarming since studies have shown that the healing process usually starts with disclosure. Moreover, little is known about the healing process of CSA experienced in the sport context. The aim of the study is to present a single case study of a CSA in sport to better understand the global experience over time from the perspective of the athlete. A narrative inquiry approach was adopted. Three non-structured interviews were conducted with the participant. Three pathways in the survivor journey have been identified through inductive thematic analysis: (a) pathway to understanding, (b) pathway to disclosure and (c) pathway to healing. These pathways represent distinct processes but are intertwined as they are dynamic and iterative. Indeed, the survivor explained how she had been, and is still, going back and forth between them. Results are consistent with those found in the literature on CSA in the general population. It suggests that theoretical models of CSA in the general population could be applied to CSA in sport. Practical implications include a need for education and clearer boundaries in the coach-athlete relationship. Sport stakeholders also need to be better equipped to recognize the signs of sexual violence in sport. Our results indicate that qualitative research could be a potential avenue to help victims heal from CSA. It gives them the chance to talk about and make sense of their abuse in a safe space. Finally, our results demonstrate the importance of reviewing the current justice system for victims. It should be based on a trauma-informed approach that places the victim at the center of the judicial process.